The connectedness between organizational time/space and experienced time/space from the perspective of an online distance student - Tran, Thi Ngan (H. : ĐHQGHN, 2020)
This research problematizes the conception of time and space in online distance education. It argues that online distance education is constructed from different times and spaces, namely those as organized by the institutions and those as experienced by the distance learners. In essence, it seeks to unfold how these organizational time and space and the experienced time and space are connected or separated, from the learners’ perspective. It employs a narrative inquiry to recount the experience of a 32-year-old British man pursuing a distance learning course. In doing this, the research aims to identify how online learners are engaged with the course that they are taking with respect to time and space, as well as pinpointing the gaps that separate them from the course. With consideration of those aspects in mind, online distance courses could be more effectively organized in such a way that enhances student motivation, commitment and resilience, thus contributing to their overall experience of digital learning.